PERANCANGAN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU BERBASIS DEKSTOP PADA SD NEGERI 272 BALLEANGING KECAMATAN UJUNGLOE - Eka Fitriani (Jurnal Sistem Informasi dan Komputer (JSIKOM), 2020)
The puspose of this research : 1. To design a new desktop trainee acceptance app at 272 Balleanging state elementary Ujung Loe Subdistict. 2. For implementing a new desktop trainee application to 272 Balleanging state elementary Ujung Loe Subdistict.The method used in this study was the development of a SDLC (Sistem Development Life Cycle) system or more often called the waterfall approach. Waterfall isa classic simple with linear model of output of each stage as input for the next step, understanding of system analysis, design of systems, coding, programming (testing), system implementation, system maintenance.The results of this experiment were to produce an app that could aid in receiving new learners at SDN 272 balleanging Ujung Loe Subdistict. The new student reception app will keep data from new trainee candidates and this will create a report of the data of new recruits that have been uploaded into the app and produced a PDF file to print and submit to the principal SDN 272 balleanging Ujung Loe Subdistict as a report